Stretching exercise to reduce musculoskeletal pain among x bakery’s workers - Dian Afif Arifah; Ani Asriani Basri (International Journal of Public Health Science (IJPHS), 2021)
X bakery has 51 workers and produces approximately 60.000 pieces of bread in a day for nine working hours. Most of the production activities are manually handled and only. The low-level musculoskeletal pain reported by 92% of packaging workers. This study aims to analyze the effectiveness and ideal duration of stretching exercise in reducing musculoskeletal disorders (MSDs) among workers. Using quasi-experimental design, 51 workers involved as respondents who were asked to do a simple stretching exercise in specific duration, five days a week in at least 4 weeks. The MSDs score were measured using the nordic body map (NBM) questionnaire. Intervention divided into 4 categories based on the duration. There is lower level of musculoskeletal pain among all exercise group in average, but comparison test doesn’t show a significant difference compared to control group (p-value=0.232). The group with 15 minutes exercise is the only group that significantly difference compared with the control group (p-value=0.020). The workers with 15 minutes stretching exercise, five days a week tend to have 5.16 % lower level of musculoskeletal pain compared to the control group. Another type of exercise and various durations might be needed as comparison to obtain more representative result.